Konseling Komunitas Melalui Pelatihan Membatik Sebagai Upaya Pemberdayaan dan Peningkatan Kemandirian Perempuan Organisasi Pemberdayaan Kesejahteraan Keluarga - Qurrota A'yuni Nur Rohmah; Ari Khusumadewi; Evi Winingsih; Budi Purwoko (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
Women are one component of society that is able to be involved in development. However, in reality, in the eyes of society, women are still considered weak creatures. Such a societal view will hinder and limit women's space for movement in the environment. Limited space for movement causes a lack of independence in women which ultimately becomes a crucial problem in society. Women who are not independent can hinder community development because they are unable to develop their potential. For this reason, the purpose of this study is to identify efforts to empower women in increasing independence through community counseling by providing batik training. The method used in this study is a literature review. The sources used in the study came from Google Scholar, Researchgate, and Publish or Perish with research limitations from 2019 to 2024. The results of the study show that community counseling with batik training can be used and is effective in increasing independence and as a means of empowering women in the PKK organization. With these activities, women in the PKK organization are able to actualize themselves by realizing their potential to then be developed optimally so that they are formed as independent and empowered individuals.